2011
DOI: 10.3390/ijms12085428
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antimicrobial and Antiproliferative Activities of Five Lichen Species

Abstract: The antioxidative, antimicrobial and antiproliferative potentials of the methanol extracts of the lichen species Parmelia sulcata, Flavoparmelia caperata, Evernia prunastri, Hypogymnia physodes and Cladonia foliacea were evaluated. The total phenolic content of the tested extracts varied from 78.12 to 141.59 mg of gallic acid equivalent (GA)/g of extract and the total flavonoid content from 20.14 to 44.43 mg of rutin equivalent (Ru)/g of extract. The antioxidant capacities of the lichen extracts were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
119
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 46 publications
11
119
5
5
Order By: Relevance
“…Atraric acid has been extracted from a bark sample contaminated by Parmelia olivetorum and P. perlata (Bourgeois et al 1999). Other authors have reported on the antimicrobial role of atraric acid in lichen species (Mitrovićet al 2011). The role that some of the hydrocarbons detected could play against microorganisms should not be left out.…”
Section: Discussionmentioning
confidence: 99%
“…Atraric acid has been extracted from a bark sample contaminated by Parmelia olivetorum and P. perlata (Bourgeois et al 1999). Other authors have reported on the antimicrobial role of atraric acid in lichen species (Mitrovićet al 2011). The role that some of the hydrocarbons detected could play against microorganisms should not be left out.…”
Section: Discussionmentioning
confidence: 99%
“…They are important in most of the ecosystem from the tropics to the polar region and include around 17,000 species [2]. The specific, even extreme, conditions of their existence, slow growth and long duration of life spans are consistent with their abundance in protective metabolite against different physical and biological influences [3][4]. The relationship between human and lichen existed since long ago.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1,050 lichen substances have been identified in the literature, and lichen secondary metabolites have diverse biological activities, including antibacterial, antiviral, antifungal, antitumor, antiherbivore, antiprotozoal, antimutagenic, antioxidant, antiinflammatory, allelochemical, analgesic, antipyretic, antiproliferative and cytotoxic effects (Müller 2001;Oksanen 2006;Molnar and Farkas 2010;Mitrović et al 2011).…”
Section: Introductionmentioning
confidence: 99%